Industrial training report: ZMY Management Services / Nur Anisah Rosli - Rosli, Nur Anisah (Universiti Teknologi MARA, Perlis, 2023)
This report is a summary of the six months I spent doing my internship training at ZMY Management Services. ZMY Management Services has been in business for more than 20 years and is able to provide a variety of services across the nation. This business provides services for personal and corporate income taxes, corporate secretaries, bookkeeping, and company incorporation. I obtain a lot of benefits from finishing my industrial training with the organization. In addition, I can experience actual working conditions while learning about the company's operations and services. My six-month internship gave me the opportunity to create the company's SWOT analysis. the advantages, risks, opportunities, and vulnerabilities. The organization can improve its weaknesses and threats while utilizing its strengths and opportunities by examining its SWOT analysis. Additionally, the business can make the effort to deal with its rivals in order to increase its chances of success. To choose services and products that a company produces better than rivals, it is critical to establish the company's competitive edge. The business can pinpoint its internal and external advantages as well as its difficulties in competing with other businesses.